A portable electrospinning apparatus based on a small solar cell and a hand generator: design, performance and application. Issue 1 (8th December 2015) - Yan, Xu; Yu, Miao; Zhang, Li-Hua; Jia, Xian-Sheng; Li, Jin-Tao; Duan, Xiao-Peng; Qin, Chong-Chong; Dong, Rui-Hua; Long, Yun-Ze
Abstract : A solar cell and hand generator operated portable electrospinning apparatus shows good flexibility and potential application in wound healing. Abstract : Electrospinning (e-spinning) devices and electrospun (e-spun) ultrathin fibers have shown promising applications in various fields. However, the poor portability of conventional e-spinning devices limits some potential applications especially in the case without a plug (electricity supply). Consequently, great efforts have been made to modify e-spinning setups with good portability. In this article, a solar cell and a hand generator-powered portable e-spinning (SHPE) setup with good flexibility is introduced, which can be used outdoors without a plug. The SHPE device shows good spinning efficacy both in solution and melt e-spinning processes for a wide range of polymers. Moreover, the designed SHPE apparatus demonstrates potential application in wound dressing by in situ e-spinning fibers onto human skin directly.